(untitled) (Revista de História da UEG (REVHIST), 2022)
This article aims at analyzing the devices that were mobilized by the military government with the objective of stimulating and promoting the displacement of groups from other regions of the country for the colonization of the Amazon. Among the colonial instruments mobilized by the government to enhance the process of the Amazon, there is the National Integration Program (PIN), signed by former President Médici, in 1970, propaganda posters of the military government in media encouraging the exploration of the Amazon and the Rural Urbanism model adopted by the National Institute for the Agrarian Reform (INCRA). For this, the theoretical contributions by Foucault are raised regarding this instrument, and approximations and relations of the colonization project undertaken by the military government with the concept of coloniality. Keywords: Amazon. Colonial instrument. Trans-amazonian.